The Effect of Mirtazapine on Cisplatin-Induced Oxidative Damage and Infertility in Rat Ovaries. (22nd April 2013) - Altuner, Durdu; Gulaboglu, Mine; Yapca, Omer Erkan; Cetin, Nihal
Abstract : Cisplatin causes infertility due to ovarian toxicity. The toxicity mechanism is unknown, but evidence suggests oxidative stress. In this study, the effect of mirtazapine on cisplatin-induced infertility and oxidative stress in rats was investigated. 64 female rats were divided into 4 groups of 16. Except for the controls that received physiologic saline only, all were administered with cisplatin (5 mg/kg i.p.) and mirtazapine (15 mg/kg p.o.) or mirtazapine (30 mg/kg p.o.) for 10 days. After this period, six rats from each group were randomly selected, and malondialdehyde (MDA), myeloperoxidase (MPO), nitric oxide (NO), total gluthatione (tGSH), gluthatione peroxidase (GPx), superoxide dismutase (SOD), and 8-hydroxy-2 deoxyguanine (8-OH Gua) levels were measured in their ovarian tissues. Reproductive functions of the remaining rats were examined for 6 months. The MDA, MPO, NO groups and 8-OH Gua levels were higher in the cisplatin-treated groups than the controls, which was not observed in the mirtazapine and cisplatin groups. GSH, GPx, and SOD levels were reduced by cisplatin, which was prevented by mirtazapine. Cisplatin caused infertility by 70%. The infertility rates were, respectively, 40% and 10% for the 15 and 30 mg/kg mirtazapine administered groups. In conclusion, oxidative stress induced by cisplatin in the rat ovary tissue causes infertility in the female rats. Mirtazapine reverses this in a dose-dependent manner.